THE RELATIONSHIP OF CORPORATE SOCIAL RESPONSIBILITY AND EMPLOYEE ENGAGEMENT CASE STUDY: PT KERETA API INDONESIA (PERSERO) - Kusumawardani, Diana; Wisesa, Anggara (Journal of Business and Management, 2018)
Abstract.Doing good or just being seen doing well is important for company these past few years. That makes corporate social responsibility as an important thing for company to create a balance between the interest of shareholders and stakeholders. In particular, corporate social responsibility is most effective when employees are actual enactors with the company acting as an enabler. It also can increase the employee engagement. Employee engagement is a concept that is judged to govern volunteer employee efforts, which means when employee have choices, they will go further for the benefit of their organization. Company reputation is one of the employee engagement drivers. Employee as the internal stakeholders has important role. Their perception on company reputation is quite important for the company reputation. Meanwhile, corporate social responsibility related with company reputation. PT Kereta Api Indonesia (Persero) is one of Stated Owned Enterprise of Indonesia which is growing rapidly in recent years. PT Kereta Api Indonesia (Persero) as SOE runs the corporate social responsibility activity. However, the corporate social responsibility activity is only for external parties. This research objective is to find the relationship of corporate social responsibility and employee engagement, the relationship of corporate social responsibility and employees’ perception on corporate social responsibility, and also the relationship of employees’ perception on corporate social responsibility on employee engagement. This research uses the quantitative approach with the number of samples 132 employees of PT Kereta Api Indonesia (Persero). Then the author uses the Structural Equation Modeling to analyze the data which shows that there is no influence of corporate social responsibility on employee engagement in PT Kereta Api Indonesia (Persero) and also there is no influence of corporate social responsibility on employee’ perception on corporate social responsibility. However there is positive influence of employee perception on corporate social responsibility on employee engagement. This research addressed to PT Kereta Api Indonesia (Persero) in order to increase the rate of employee engagement in the company and maximize the benefit of corporate social responsibility for human resource aspect.Keywords: corporate social responsibility, employee engagement, employee perception of corporate social responsibility